2015
DOI: 10.3109/02656736.2015.1075606
|View full text |Cite
|
Sign up to set email alerts
|

Lack of significant intraoperative coagulopathy in patients undergoing cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (HIPEC) indicates that epidural anaesthesia is a safe option

Abstract: Our results support the belief that epidural analgesia is a safe option in cytoreductive surgery and HIPEC despite certain intraoperative fluctuations in coagulation parameters. It is of major importance to regulate any abnormalities observed during surgery. There are no available data regarding the occurrence of coagulopathy in the post-operative period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…Additionally, the procedure has been depicted as a high risk with significant levels of comorbidity (22–39%), mortality (5%) and prolonged hospital stays [ 11 ]. Although cytoreductive surgery (CRS) and hyperthermic intraperitoneal preoperative chemotherapy (HIPEC) have established its therapeutic role in selected patient populations with peritoneal carcinomatosis (PC), multiple factors can disrupt the patient metabolism during and after surgery [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the procedure has been depicted as a high risk with significant levels of comorbidity (22–39%), mortality (5%) and prolonged hospital stays [ 11 ]. Although cytoreductive surgery (CRS) and hyperthermic intraperitoneal preoperative chemotherapy (HIPEC) have established its therapeutic role in selected patient populations with peritoneal carcinomatosis (PC), multiple factors can disrupt the patient metabolism during and after surgery [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, epidural analgesia should be used with caution in patients with CRS and HIPEC. Although not many cases are reported of coagulation abnormalities that are insufficient to maintain and remove the epidural catheter after surgery [ 17 ], but massive bleeding may occur during the surgery, according to the severity or invasiveness of the cancer. Hurdle et al [ 18 ] reported that postoperative coagulopathy occurred in approximately 40% of patients who underwent CRS with HIPEC, and the incidence was higher with intraoperative blood transfusion or higher PCI scores.…”
Section: Discussionmentioning
confidence: 99%
“…TEA combined with opioids has the advantages of analgesia, early extubation after surgery, lower postoperative pulmonary complications, and reduced incidence of postoperative complications [67][68][69][70] TEA is a safe option for CRS + HIPEC treatment, regardless of some fluctuations in intraoperative coagulation measurements [71,72]. [62].…”
Section: Regional Nerve Blockmentioning
confidence: 99%
“…However, there are controversies in the implementation of TEA, since HIPCE could affect blood coagulation and cause thrombocytopenia [68]. A recent prospective clinical study indicated that TEA is a safe option for CRS + HIPEC treatment, regardless of some fluctuations in intraoperative coagulation measurements [71]. Chua et al investigated 4277 patients who received the CRS + HIPEC treatment and found no postoperative epidural hematoma in these patients [72].…”
Section: Regional Nerve Blockmentioning
confidence: 99%